Risk Management Strategies in Derivatives Markets - Bakoeva Gulbakhor (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This paper explores risk management strategies employed in the derivatives markets, focusing on the use of financial instruments such as futures, options, forwards, and swaps to hedge market exposure. It discusses how investors, corporations, and financial institutions use derivatives to mitigate price volatility, interest rate fluctuations, and currency risks. The article also analyzes regulatory frameworks and lessons learned from financial crises, providing evidence from both developed and emerging markets.